2021
DOI: 10.1002/14651858.cd007337.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal local anaesthetic instillation versus no intraperitoneal local anaesthetic instillation for laparoscopic cholecystectomy

Abstract: Intraperitoneal local anaesthetic instillation versus no intraperitoneal local anaesthetic instillation for laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…Various systematic reviews and meta-analyses pool and analyze the existing literature 5,19,20 . Loizides et al concluded that there is a very low level of scientific evidence in favor of infiltration of incisional sites, with a reduction in POP in patients with low anesthetic risk and little clinical relevance derived from it.…”
Section: Discussionmentioning
confidence: 99%
“…Various systematic reviews and meta-analyses pool and analyze the existing literature 5,19,20 . Loizides et al concluded that there is a very low level of scientific evidence in favor of infiltration of incisional sites, with a reduction in POP in patients with low anesthetic risk and little clinical relevance derived from it.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no unifed protocol is available to provide standardized interventions for pain relief after LC. Various pharmacological and nonpharmacological measures have been clinically explored to address pain after LC, such as local anesthetics [4], transversus abdominis plane block [5], and low-pressure pneumoperitoneum [6] which needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…A local anesthetic can be administered through a variety of approaches, including intravenous injections, incision infiltration, and transversus abdominis plane (TAP) blocks, among others, of which intraperitoneal local anesthesia (IPLA) is a popular method [16][17][18][19]. Although IPLA is effective in many abdominal surgeries, many controversies surround bariatric surgery [14,[20][21][22]. No meta-analysis has been carried out on this topic to collect evidence of high-quality support points to an urgent need for research in this area.…”
Section: Introductionmentioning
confidence: 99%